2020
DOI: 10.1007/s00345-020-03512-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic simple prostatectomy vs bipolar plasma enucleation of the prostate in large benign prostatic hyperplasia: a two-center 3-year comparison

Abstract: Purpose To compare surgery outcomes and safety of button bipolar enucleation of the prostate vs laparoscopic simple prostatectomy in patients with large prostates (> 80 g) in a two-center cohort study. Methods All patients with lower urinary tract symptoms due to benign prostatic enlargement (Prostate volume > 80 cc) undergoing button bipolar enucleation of the prostate (BTUEP) or laparoscopic simple prostatectomy (LSP) in two centers were enrolled. Data on clinical history, physical examination, urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Our findings are broadly consistent with previously published literature. This suggests that even though there are some differences between the different surgical procedures, they appear to be equally effective for treatment of large BPH (19). Furthermore, it should be noted that we also observed that EEP had a superior 6-month PVR (only two studies involved), but this conclusion needs to be confirmed in high-quality randomized controlled trials (RCTs) with longer follow-up.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Our findings are broadly consistent with previously published literature. This suggests that even though there are some differences between the different surgical procedures, they appear to be equally effective for treatment of large BPH (19). Furthermore, it should be noted that we also observed that EEP had a superior 6-month PVR (only two studies involved), but this conclusion needs to be confirmed in high-quality randomized controlled trials (RCTs) with longer follow-up.…”
Section: Discussionmentioning
confidence: 63%
“…There was no difference in 3-month QoL (MD −0.13, 95% CI −0.79 to 0.52, p = 0.69). Furthermore, four studies (13,14,17,19) reported the postoperative PSA (Figure 3), and MISP had the same PSA as the EEP group during short-term follow-up (MD −0.19, 95% CI −0.55 to 0.18, p = 0.33). Of note, there was significant heterogeneity among studies (p < 0.10) for each metric.…”
Section: Efficacy Outcomesmentioning
confidence: 96%
See 3 more Smart Citations